about Iceo

Discussion in 'Homework Help' started by stupid, Apr 29, 2010.

  1. stupid

    Thread Starter Active Member

    Oct 18, 2009
    i m having trouble to make sense of common emitter config.
    the book says for a common-base config the base-emitter is forward biased while collector-base is reversed & so with common emitter config.
    & go on to derive Iceo based on above statement.
    Iceo= Icbo/(1-α) where Iceo is collector-emitter reversed current when Ib=0, Icbo is collector-base reversed current when Ie=0.

    shouldnt common emitter config has collector-emitter reversed?

    i think Icbo doesnt belong to common emitter config as that implies Ie=0 which is not the case.

    i dun understand why he used the common base config parameters to derive Iceo that is for common emitter which clearly has collector-emitter reverse biased.

    my assumption for Iceo.
    Ic = αIe + Iceo
    Iceo = Ic - αIe
    =Ic - α(Ic + Ib)
    rearrange, Ic = (Iceo+αIb)/(1-α)

    Iceo= Ic(1-α)-αIb

    when Ib=0
    Iceo= Ic(1-α)

    is that a right assumption?

    Last edited: Apr 29, 2010